Cocreation from Emerging Opportunities: Occupational Therapists' Perspectives on Supporting Older Persons, in Japan. (21st July 2022) - Bontje, Peter; Josephsson, Staffan; Tamura, Yumi; Ishibashi, Yu; Sakane, Yuki; Horibe, Yasuyo; Asaba, Eric
Abstract : Introduction . Practices of occupational therapists, particularly those supporting older persons with physical impairments, remain overly focused on remediating impairments, and implementation of occupation-centered practices remains fraught with difficulties. In Japan, this issue exists across the continuum from acute care to rehabilitation settings and into the community. This is despite the existence of international models and frameworks that place occupation at the core of the profession. Accordingly, there is a need to better understand how occupational therapists respond to the call for occupation-centered practices across the said continuum of care with this population. The aim of this study was at exploring and understanding occupational therapists' experiences of supporting the resumption of occupations among older persons with physical impairments, in Japan. Methods . Embedded in a constructivist world view, this was a qualitative focus group study. Four focus groups (two in urban areas and one each in rural and semirural areas), consisting of seven or eight occupational therapists with at least three years of relevant practice experience, convened twice to narrate and explore their support of older persons. All were participating voluntarily with confidentiality of their participation being guaranteed by the researchers. They met for a third time to verify emerging analytic results. Data were analysed using a reflective thematic analysis. Results . Identified were three themes, namely, calling forth powers of occupations, imagining client's future, and cocreating plots, which we synthesized into recurring cocreations from emerging opportunities. Discussion . Supporting the resumption of occupations among older persons with physical impairments hinges on repeated processes of identifying possibilities for occupation, followed by actions to bring these (e.g., images of clients' future) into reality. Occupations' healing properties (i.e., occupations' powers) can be used to assist clients in experiencing health and well-being. The results suggest a reframing of occupational therapy practices as recurring processes of recognizing opportunities for occupation, followed by actions whereby these possibilities are turned into reality. Occupational therapy effectiveness might be enhanced when goals and methods are repeatedly and creatively aligned with the evolving plots cocreated between the client, therapist, and stakeholders.